SULA’S EXISTENTIAL FREEDOM IN TONI MORRISON’S NOVEL ENTITLED SULA - Asmarani, Ratna (Balai Bahasa Jawa Timur, 2014)
This paper aims to analyze the problems concerning the existential freedom of the young, black, female, main character. Several concepts are used in the analysis; namely, black women existentialism, existential backlash, power feminism, and black feminism. The analysis is also done in the frame of feminist criticism. The result of the analysis shows that it is not easy for a young, black, female character to construct, keep, and/or perform her critical opinion concerning her own existential freedom. There are various kinds of existential backlashes that have to be faced by the female character. Finally, the female character who insists on keeping her own critical opinion concerning her own existential freedom, after she fails to put it into practice in daily life, still has to face a tragic ending. This paper aims to analyze the problems concerning the existential freedom of the young, black, female, main character. Several concepts are used in the analysis; namely, black women existentialism, existential backlash, power feminism, and black feminism. The analysis is also done in the frame of feminist criticism. The result of the analysis shows that it is not easy for a young, black, female character to construct, keep, and/or perform her critical opinion concerning her own existential freedom. There are various kinds of existential backlashes that have to be faced by the female character. Finally, the female character who insists on keeping her own critical opinion concerning her own existential freedom, after she fails to put it into practice in daily life, still has to face a tragic ending Abstrak: Makalah ini bertujuan untuk mengkaji permasalahan seputar kebebasan eksistensial tokoh utama perempuan muda kulit hitam. Beberapa konsep digunakan dalam kajian; yaitu, eksistensialisme perempuan kulit hitam, lecut balik eksistensial, feminisme yang mengandalkan kekuatan, dan feminisme kulit hitam. Kajian juga dilakukan dalam kerangka kritik feminis. Hasil kajian menunjukkan bahwa tidak mudah bagi perempuan muda kulit hitam untuk mengkonstruksi, menyimpan, dan/atau menerapkan pemikirannya yang kritis berkenaan dengan kebebasan eksistensialnya sendiri. Ada berbagai lecut balik eksistensial yang harus dihadapinya. Akhirnya, tokoh perempuan yang bersikeras menyimpan pemikirannya yang kritis berkenaan dengan kebebasan keberadaannya tersebut, setelah ia gagal menerapkannya dalam kehidupan sehari?hari, masih harus menghadapi akhir yang tragis. Kata-Kata Kunci: eksistensialisme perempuan kulit hitam; lecut balik eksistensial; feminisme yang berbasis kekuatan; feminisme kulit hitam.